Penyelesaian Perkara Tindak Pidana Anak Dibawah Umur Dengan Asas Restorative Justice di Lingkungan Polres Belitung Timur - Revaldy Nugraha; I Made Kanthika; Markoni Markoni; Helvis Helvis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Crimes of theft in the family committed by children require special handling by the police, not all cases involving children are resolved through the courts. This is in the best interests of the child and also considers justice for the victim, which is called a restorative justice approach. This research aims to analyze the form of resolution of criminal acts committed by minors in the East Belitung Police area. The results of the research are that the resolution of children's cases that applies restorative justice is guided by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and the 2012 Political Regulations concerning Restorative Justice, namely the resolution of children's cases outside the criminal court which emphasizes restoring the situation. initially with an emphasis on conditions for creating justice and balance for children and their victims. The conclusion is that the form of resolving criminal acts of theft committed by the East Belitung Police is by implementing restorative justice. Restorative justice carried out by the East Belitung Police aims to accommodate the norms and values ​​that apply in society while providing legal certainty, especially the benefits and a sense of justice that meets the needs of the community. a sense of justice for all parties, which is a manifestation of the National Police's authority in carrying out duties in the field of criminal proceedings and police discretion based on Articles 16 and 18 of Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia.